Multigene phylogeny and morphology reveal Cytospora spiraeae sp. nov. (Diaporthales, Ascomycota) in China - Zhu, Hai-Yan; Tian, Cheng-Ming; Fan, Xin-Lei (Phytotaxa, 2018)
Members of Cytospora encompass important plant-associated pathogens, endophytes and saprobes, commonly isolated from a wide range of hosts with a worldwide distribution. Two specimens were collected associated with symptomatic canker and dieback disease of Spiraea salicifolia in Gansu, China. These isolates are characterized by its hyaline, biseriate, aseptate, elongate-allantoid ascospores and allantoid conidia. Cytospora spiraeae sp. nov. is introduced based on its holomorphic morphology plus support from phylogenetic analysis (ITS, LSU, ACT and RPB2), and differs from similar species in its host association.